Upaya Meningkatkan Kebersihan Lingkungan Melalui Gotong Royong dan Les Calistung Gratis Kepada Siswa SD Kelas 1 di Desa Pagar Batu - Eltri Yanti Pakpahan; Tetty Silitonga (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research evaluates the effect of the mutual cooperation program and free Calistung learning for grade 1 elementary school students in Pagar Batu village on improving environmental cleanliness and academic skills. The research method uses a participatory approach where parents, teachers and the local community are actively involved. The implementation of the mutual cooperation program has succeeded in making people aware of the importance of maintaining a clean environment. Regular mutual cooperation creates a cleaner and healthier environment. Calistung Tutoring fees have a positive impact on students' academic abilities, especially reading and mathematics abilities. By working together, the community participates in cleaning up the surrounding environment, including cleaning blocked drains. Tutoring Calistung, meanwhile, takes place under the guidance of a qualified teacher or volunteer. The material is adapted to the elementary school curriculum to improve students' academic abilities. This program has good potential to improve environmental cleanliness and student academic achievement. Recommendations include increasing the number of stakeholders and expanding the program so that its impact on society is broader and more sustainable.